Pengaruh Penggunaan Media Sosial Tiktok terhadap Tingkat Interaksi Sosial Siswa Kelas VII di SMP Negeri 17 Kota Jambi - Sofiatun Nisa; Nelyahardi Gutji; Fellicia Ayu Sekonda (Departement of Mathematics Education, 2023)
Social media is a network that is very easy to access as a means of surfing in cyberspace, especially the social media tiktok. There are lots of benefits that can be taken by users who use this application, for example, is interacting with friends. This study aims to reveal the effect of the level of use of social media tiktok on the level of social interaction of class VII students at SMP Negeri 17 Jambi City. This type of research is quantitative with ex post facto method. The technique used in collecting data is by using a questionnaire, and to determine the accuracy of the instrument validity and reliability tests are carried out. Then the data analysis technique used was formula C, normality test, linearity test, and simple regression analysis with the help of the SPSS 24 program. The technique used in sampling was purposive sampling technique with a sample size of 79 students from 239 students. . The results of the study show that the effect of using social media tiktok on the level of social interaction of class VII students at SMP Negeri 17 Jambi City is at a percentage of 11.2% or 0.112 with a low but definite classification. The level of social media use by students is 63.89% which is included in the high category. While the level of social interaction of students of 64.57% is included in the high category.